2013
DOI: 10.1371/journal.pone.0060783
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-Motor Interactions for Vocal Pitch Monitoring in Non-Primary Human Auditory Cortex

Abstract: The neural mechanisms underlying processing of auditory feedback during self-vocalization are poorly understood. One technique used to study the role of auditory feedback involves shifting the pitch of the feedback that a speaker receives, known as pitch-shifted feedback. We utilized a pitch shift self-vocalization and playback paradigm to investigate the underlying neural mechanisms of audio-vocal interaction. High-resolution electrocorticography (ECoG) signals were recorded directly from auditory cortex of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 51 publications
7
77
0
Order By: Relevance
“…Such recordings further refine our understanding of the spatial distribution of neural networks involved in auditory feedback processing during speaking (Chang et al, 2013; Greenlee et al, 2013). Results of those studies have shown that spatially segregated sub-regions within higher order auditory cortex on posterolateral STG exhibited neural responses to pitch shifts that are modulated during speaking compared with playback.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Such recordings further refine our understanding of the spatial distribution of neural networks involved in auditory feedback processing during speaking (Chang et al, 2013; Greenlee et al, 2013). Results of those studies have shown that spatially segregated sub-regions within higher order auditory cortex on posterolateral STG exhibited neural responses to pitch shifts that are modulated during speaking compared with playback.…”
Section: Discussionmentioning
confidence: 83%
“…By recording electrocorticograms (ECoG) in those subjects, we have described auditory cortical responses after perturbed and unperturbed feedback states and reported neural response changes and the correlation of those changes with vocal behavior (i.e. compensation) in response to pitch shifts (Greenlee et al, 2013). Because ECoG provides limited anatomic sampling of only portions of an individual brain, we have begun using fMRI to provide greater anatomic sampling to supplement the insights gained from ECoG Recordings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intentional behaviors including the voice are generally thought to involve prefrontal mechanisms (Koval et al, 2011;Schafer and Moore, 2011). Reports using functional magnetic resonance imaging (fMRI) or electrocorticography (ECoG) methods suggest the superior temporal gyrus and premotor cortex are involved in the pitch-shift reflex (Parkinson et al, 2012;Greenlee et al, 2013). Thus far, there is no evidence that prefrontal cortex is involved in responses to pitch-shift stimuli.…”
Section: Discussionmentioning
confidence: 99%